Mental spaces in grammar : conditional constructions - Dancygier, Barbara (Cambridge studies in linguistics., 2005)
Conditional constructions have long fascinated linguists and philosophers. In this pioneering study, Barbara Dancygier and Eve Sweetser offer a new descriptive framework for the study of conditionality, broadening the range of richly described conditional constructions. This significant contribution to the field will be welcomed by theoretical and cognitive linguists alike.